Hydrogeology and hydrogeochemistry of the geothermal systems and its direct use application: Balçova-Narlıdere geothermal system, İzmir, Turkey. (September 2022) - Baba, Alper; Sözbilir, Hasan; Sayık, Tolga; Arslan, Sinan; Uzelli, Taygun; Tonkul, Serhat; Demir, Mustafa M.
Highlights: District heating systems are based on the principle that the geothermal system's fluid flows to the surface from production wells, and is delivered to buildings by distribution pipes. Many countries are starting to use their geothermal resources in district heating. The Balçova-Narlıdere geothermal field is the first field to have its geothermal energy actively explored with advanced technological and scientific methods in Turkey. The levelized cost of heat from geothermal district heating systems compares favorably with other fuel sources. It is crucial to accelerate studies on the use of geothermal resources to heat and cool cities. Abstract: The Balçova-Narlıdere geothermal system, located in western Turkey, is an extensional domain type geothermal play. Geological, hydrogeological, and geothermal studies have been done in the Balçova-Narlıdere geothermal field since 1960. As a result of these studies, production and research wells were drilled in the area by both the public and private sectors. Of the 37 wells drilled in the Balçova-Narlıdere geothermal field, 26 were drilled by İzmir Geothermal Energy Company Inc. (16 productions, 4 re-injection, 4 gradientst, 2 unused) and 11 by the İzmir Governorship Investment Monitoring and Coordination Department and companies in the private sectors. There are two reservoirs, one shallow and one deep, in the geothermal field. Well depths are less than 200 m in the shallow reservoir. The deep production wells have depths ranging from 400 to 1, 100 m and reservoir temperatures reaching 140 °C. The electrical conductivity (EC) values in the shallow production wells range from 1, 200 to 1, 500 µS/cm. EC values in the deep production wells vary from 1, 871 to 2, 025 µS/cm, and all geothermal fluids in the field are mineral-rich waters. In the İzmir geothermal district heating system, the newest technologies are used, and operational costs are very low. İzmir Geothermal Energy Company Inc. has been operating since 1996 and has reached 38, 460 residences. The current capacity of the system is approximately 160 MWt. Cooling systems continue to spread in Turkey, focusing on electric air conditioning systems and geothermal heating systems, but both economic and applicability problems have slowed the expansion of cooling systems. However, İzmir Geothermal Energy Company Inc. began operating its first geothermal cooling application in Balçova in 2018, cooling 1, 900 m 2 of the indoor area by lithium bromide absorption and 90/85 °C geothermal temperature regime by supplying 6/9 °C clean cold water to the coolers in the buildings. These results show that the extensional domain type geothermal system in the Balçova-Narlıdere region is suitable for both heating and cooling applications.